Bilateral Mesenchymal Hamartoma of the Chest Wall in a 3-Month-Old Boy: A Case Report and Review of the Literature - Mona Alfaraidi; Hossam Alaradati; Irfan Mamoun; Shamayel Mohammed (Case Reports in Pathology)
Mesenchymal hamartoma of the chest wall is a well-recognized but extremely rare entity. This entity is believed to be benign with no propensity for invasion or metastasis. Although the lesion manifests with alarming aggressive clinical, radiological, and histological features, it is considered benign and carries an excellent outcome. Therefore it is important to recognize this benign entity to avoid the possible misdiagnosis of malignancy and the unnecessary use of chemotherapy. We present a case of bilateral multifocal mesenchymal hamartomas of the chest wall in a male infant and a literature review of this entity. Our aim is to improve the awareness of this condition and highlight its benign behavior and satisfactory outcome following complete surgical resection.